Comparative evaluation of flexural strength of type II type VII and nano based glass ionomer cement - In vitro (Cuestiones de Fisioterapia, 2023)
Introduction:- The capacity of a material to withstand bending forces applied perpendicular to its longitudinal axis is known as flexural strength. It is a phrase that is frequently used in dentistry. Megapascals, or MPa, are the metric units used to describe it. Glass ionomer cements (GICs) are aesthetically pleasing dental products with special qualities that make them effective as luting and restorative materials. GIC cements come in a total of 9 varieties